2023
DOI: 10.1017/erm.2023.13
|View full text |Cite
|
Sign up to set email alerts
|

Targeting N-cadherin (CDH2) and the malignant bone marrow microenvironment in acute leukaemia

Abstract: This review discusses current research on acute paediatric leukaemia, the leukaemic bone marrow (BM) microenvironment and recently discovered therapeutic opportunities to target leukaemia–niche interactions. The tumour microenvironment plays an integral role in conferring treatment resistance to leukaemia cells, this poses as a key clinical challenge that hinders management of this disease. Here we focus on the role of the cell adhesion molecule N-cadherin (CDH2) within the malignant BM microenvironment and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…Dysregulation of E-cadherin protein expression leads to the loss of the adhesion ability of tumor cells and contributes to the metastasis of tumor cells ( 35 ). Moreover, previous studies have reported that N-cadherin can induce tumor cell invasion and angiogenesis ( 36 , 37 ), and a number of N-cadherin antagonists have been adopted for tumor therapy ( 38 ). The present study demonstrated that DEX-HCl combined with SFC significantly upregulated E-cadherin and significantly downregulated N-cadherin protein expression levels, thereby inhibiting KYSE30 cell metastasis and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of E-cadherin protein expression leads to the loss of the adhesion ability of tumor cells and contributes to the metastasis of tumor cells ( 35 ). Moreover, previous studies have reported that N-cadherin can induce tumor cell invasion and angiogenesis ( 36 , 37 ), and a number of N-cadherin antagonists have been adopted for tumor therapy ( 38 ). The present study demonstrated that DEX-HCl combined with SFC significantly upregulated E-cadherin and significantly downregulated N-cadherin protein expression levels, thereby inhibiting KYSE30 cell metastasis and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that the dysfunction of osteolineage cells in the BM niche can induce myelodysplasia and leukemia [57]. Consequently, the LSCinduced microenvironment creates novel environmental conditions that protect leukemia cells from chemotherapy [59]. For example, classical chemotherapeutic agents that cause DNA damage or spindle poisoning target actively proliferating cells and therefore cannot be used effectively against quiescent LSCs in the BM niche [60].…”
Section: Maintaining and Keeping Of Hematopoietic Stem Cells (Hscs) I...mentioning
confidence: 99%
“…N-cadherin is expressed in various cell types that reside in BM niches: these cells are osteoblasts and MSCs in the endosteal niche, and endothelial cells and pericytes in the perivascular niche [102]. Osteoblasts, which play a critical role in establishing and maintaining the required niche microenvironment, and in regulating stem cell quiescence and proliferation, express N-cadherin in the BM niche [59,103]. Although earlier reports suggested that loss of N-cadherin in osteoblasts or HSCs would not have a deleterious effect on hematopoiesis, recent studies have shown that osteoblast-dependent regulation of HSCs in the BM niche is directly related to homophilic N-cadherin interactions between osteoblasts and HSCs [104,105].…”
Section: N-cadherin In Acute Leukemiamentioning
confidence: 99%